Production Of Vinyl Chloride Based Polymer - Ismoilova H.Dj (Research Parks Publishers, 2022)
Viniplast is characterized by mechanical prochnostyu, v 5 times legche chuguna, v 8 raz legche svintsa, nizkoy teploprovodnostyu.Iz nego izgotovlyayut pokrytiya эlektroliznyx vann, ventilyatsionnyx ustroystv, pogloshchayushchix parы acid, bakov dlya acid i shchelochey